An agent-based model schema to understand how shocks to the household a ect energy consumption behaviour - Wood, Katherine (Cranfield University, 2014)
There are many factors which are understood to a ect domestic energy consumption, including: occupant demographics such as age, income and family type, occupant attitudes, peer networks and occupant-building interactions such as window opening, heating and lighting patterns. Both top-down and bottom-up modelling approaches have been used previously to represent these behavioural factors and other domestic energy usage variables such as dwelling construction. Top-down models were found to lack the granularity and exibility to accurately portray the UK domestic energy sector from the perspective of individual households. Conversely, bottom-up models were found to be more applicable to behavioural factors due to their ability to model individual entities and interactions. However, it was also identi ed that most current models only consider building construction or occupant behaviour, with few combining the two. This project aims to combine occupant behaviour and dwelling construction variables by suggesting an agent-based model implementation schema to provide insight into the domestic energy consumption system, with special interest in the e ects of life-stage changes on the household and the e ect of peer networks on the adoption of energy e ciency measures. Five `shock' groups are considered, namely, households a ected by a recent: retirement, unemployment, new child, house move or reduction in household size. A pilot survey was conducted in order to obtain results to inform model design decisions and the results are discussed.